(untitled) (PERcursos Linguísticos, 2020)
We aim to investigate how death, considered a borderline moment for human existence, is configured in the narrative written by Guimarães Rosa, a Brazilian writer. The narrative is called “Fatalidade” and it is part of the book “Primeiras Estórias”. We use the methodology of discursive semiotics, a struturalist theory and methodology born in the 1960s by Greimas and other scholars in France. We also use the contribuitions of the tensivity approach of semiotics, especially those coming from the semioticist Claude Zilberberg, such as the concepts of intensity and extensity. We have proved that the tensivity hypothesis is useful for understanding how the actors relate to the waiting of death in the narrative context.